Education and NGOs - Pe Symaco, Lorraine (London Bloomsbury, 2016)
"Education and NGOs discusses the role of sectors outside the mainstream in relation to improving access to education, with particular focus on the underprivileged. International case study examples offer insights into the work of non-governmental organizations, which play a crucial role in UNESCO's global Education for Sustainable Development (ESD) effort, by providing alternative forms of education and improving educational access.Including a discussion of the work of organizations such as Africa Educational Trust, Kids Company, FIDAL Foundation and many others, the volume explores the role of NGOs in the UK, the USA, India, Nepal, the Gaza Strip, Ecuador, Philippines and South Africa. Each chapter contains contemporary questions to encourage active engagement with the material and an annotated list of suggested reading to support further exploration"--
"Education and NGOs discusses the role of sectors outside the mainstream in relation to improving access to education, with particular focus on the underprivileged. International case study examples offer insights into the work of non-governmental organizations, which play a crucial role in UNESCO's global Education for Sustainable Development (ESD) effort, by providing alternative forms of education and improving educational access. Including a discussion of the work of organizations such as Africa Educational Trust, Kids Company, FIDAL Foundation and many others, the volume explores the role of NGOs in the UK, the USA, India, Nepal, the Gaza Strip, Ecuador, Philippines and South Africa. Each chapter contains contemporary questions to encourage active engagement with the material and an annotated list of suggested reading to support further exploration"--
Machine generated contents note: -- Series Editor's Preface -- Introduction, Lorraine Pe Symaco (University of Malaya, Malaysia) -- 1. The Role of NGOs in Supporting Education in Africa, Michael Brophy -- 2. Education and NGOs in Ecuador, Rosalia Arteaga (Advisory Council of the Latin American Foundation for the Integration and Development) -- 3. Non-Governmental Provision of Education for Children in the Gaza Strip, Lucy Thirkell (University of Cambridge, UK) -- 4. Going to School Programme in India, Ch. Radha Gayathri (Jawaharlal Nehru University, India) and Lisa Heydlauff (Going to School, India) -- 5. High Impact Tourism Training (HITT) Programme in Nepal, Jonathan Demenge (Swiss Agency for Development and Cooperation, Switzerland) and Bibek Shrestha (Alternative Energy Promotion Centre, Nepal) -- 6. Education and NGOs in the Philippines, Benjamin Diokno (University of the Philippines, Philippines) and Lorraine Pe Symaco (University of Malaya, Malaysia) -- 7. The Work of Borien Educational Foundation for Southern Africa (BEFSA) in the Eastern Cape, Keith Borien (Borien Educational Foundation for Southern Africa, South Africa) -- 8. Educating Vulnerable Children in the UK, Camila Batmanghelidjh (Kids Company, UK) -- 9. The Role of NGOs and Educational Partnerships in the USA, Caroline Collins (University California, San Diego, USA) -- Index.
Keywords: Education; Educational change; Non-governmental organizations; EDUCATION / Comparative; EDUCATION / Multicultural Education